2007
DOI: 10.1179/174328407x176956
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and formation of boundary in laser cladding AZ91D with Al + Al2O3

Abstract: The laser surface cladding of AZ91D magnesium alloy with AlzAl 2 O 3 powders was investigated. The growth morphology of the boundary zone between the laser surface cladding layer and AZ91D substrate, and the distribution of Al 2 O 3 particles in the laser surface cladding layer, were observed by optical microscope and scanning electron microscope. Furthermore, the element line and mapping scans analyses on the boundary zone were carried out with energy dispersive spectrum. The phases in the laser cladding laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…C. J Chen et al [3] studied laser surface cladding of AZ5 magnesium alloy with pre-placed nano-Al 2 O 3 by the use of Nd:YAG laser, the results show that the micro-hardness of the alloy was improved 3.5 times, the wear resistance of the alloy was significantly improved. In recent years, the research of laser surface modification on magnesium alloys was focus on Al-based coating [4,5], Cu-based coating [6,7], ceramics coating [8] and composite coating [9].…”
Section: Introductionmentioning
confidence: 99%
“…C. J Chen et al [3] studied laser surface cladding of AZ5 magnesium alloy with pre-placed nano-Al 2 O 3 by the use of Nd:YAG laser, the results show that the micro-hardness of the alloy was improved 3.5 times, the wear resistance of the alloy was significantly improved. In recent years, the research of laser surface modification on magnesium alloys was focus on Al-based coating [4,5], Cu-based coating [6,7], ceramics coating [8] and composite coating [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that nanometer-sized materials can exhibit different structures and properties compared with those of the corresponding bulk materials because of the size effect [5][6][7][8][9][10][11][12]. Although Ag nanoparticles and Ag NWs, in most cases, have a face-centered cubic (fcc) structure (the same as that of bulk silver) [13][14][15][16][17][18][19][20][21][22], a hexagonal 4H structure was first discovered in nanocrystalline silver by Taneja et al several years ago [23]. Thereafter, Zhu's group [24,25] fabricated 4H-Ag NWs by the process of electrochemical deposition on porous anodized aluminum oxide templates, and they revealed that the highest occurrence of 4H-Ag NWs, among the total Ag NWs, was at diameters around 30 nm.…”
Section: Introductionmentioning
confidence: 99%